Regulatory and policy tools to address unproven stem cell interventions in Canada: the need for action - Timothy Caulfield (BMC Medical Ethics, 2019)
Abstract Background The marketing of unproven direct-to-consumer stem cell interventions is becoming widespread in Canada. There is little evidence supporting their use and they have been associated with a range of harms. Canada has been slower to act against clinics offering these interventions than other jurisdictions, including the United States. Here, we outline the regulatory and policy tools available in Canada to address this growing problem. Main body Health Canada’s regulations governing cell therapies are complex, but recent statements make it clear that Health Canada believes it has jurisdiction over many of the currently marketed stem cell interventions. Still, further regulatory clarity is needed from Health Canada, as are increased directed enforcement efforts on interventions that fall within their scope. The Competition Bureau, via the Competition Act, prohibits advertisers from making materially false or misleading promotional representations. The Competition Bureau could collaborate with the scientific community to analyze the claims of existing clinics in Canada, and impose sanctions upon those who breach the established standard. Professional regulators, including provincial colleges of physicians and surgeons, have considerable power over what products and services their members can offer. Every college of physicians in Canada requires, via policy and codes of ethics, that doctors maintain evidence-based practices. This requirement is incompatible with offering many unproven stem cell interventions. Litigation may be another tool, including the use of fraud, misrepresentation and/or negligence claims for failing to meet the required standard of care. Finally, political pressure on federal and provincial lawmakers could encourage changes to marketing, cell therapy and professional regulations that would allow a more comprehensive response. Conclusions In sum, there are many existing tools that can be used to protect the public from unproven stem cell interventions. Increased bureaucratic will and grassroots efforts are needed in order to effect a positive policy response.